Pengembangan Media Podcast untuk Pembelajaran Dialog Bahasa Jawa Kelas VII di SMP Negeri 3 Semarang (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
Curriculum 2013 Javanese language level basic competency dialogue/conversation prioritizes the verbal ability of students. Unggah-ungguh requires more refraction and understanding to be applied in a real conversationThis indicates that listening media such as relevant for the learning process of dialogue/conversation. This study aims to, (1) identify the needs of educators and students to podcast media for learning dialogue Javanese language grade VII junior high school level, (2) develop a prototype form of podcast media for learning dialogue Javanese language grade VII junior high school level, (3) describe the results of expert validation of podcast media for learning dialogue Javanese grade VII junior high school level. This type of research is Research and Development (R&D) with five stages. The results showed that educators and students need podcast media for learning Javanese dialogue. This research successfully developed a podcast-based learning media with the title Podcast Pak Jaka "Pacelathon Kawruh Jawa lan Kabudayan". The research products then assessed by material and media experts. The results of these assessments are used as a basis for improving media to be appropriate for use in learning. Keywords: learning media, podcasts, pacelathon, Javanese dialogue.